A Descriptive Mixed-Methods Analysis of Sexual Behavior and Knowledge in Very Young Children Assessed for Sexual Abuse: The ASAC Study - Vrolijk-Bosschaart, T. F.; Brilleslijper-Kater, S. N.; Verlinden, E.; Widdershoven, G. A. M.; Teeuw, A. H.; Voskes, Y.; van Duin, E. M.; Verhoeff, A. P.; de Leeuw, M.; Roskam, M. J.; Benninga, M. A.; Lindauer, R. J. L. (Frontiers in Psychology, 2019)
Child sexual abuse (CSA) is a worldwide problem with serious consequences. We hypothesized that worrisome sexual behavior and knowledge would frequently be reported in children assessed after CSA. We therefore investigated (A) what types of sexual behaviors and knowledge were reported by parents of young children assessed for CSA; (B) in what cases such behaviors and knowledge were worrisome; and (C) how such children responded verbally and non-verbally during child interviews. We conducted a mixed-methods study, including qualitative inductive content analysis and quantitative analysis. It included 125 children (76 boys, 60.8%; median age 3.3 years, age range 0–11), all involved in the Amsterdam sexual abuse case (ASAC) and examined for highly suspected (n = 71) or confirmed CSA (n = 54). We identified themes from (1) the parent reports: sexual behavior (e.g. self-stimulation, touching others, imitation of sexual acts), fears and anxiety with regard to sexuality, and sexual utterances (sexual slang, references to sexual acts); and (2) the child interviews: behavioral reactions (avoidance, distractive behaviors), emotional reactions (anger, aggression), and verbal reactions (conspicuous utterances, refusal to talk about specific subjects). In 37% of the children the sexual behavior was deemed worrisome or very worrisome. Clinicians who assess children for CSA are advised to focus in particular on sexual behavior problems and inappropriate sexual knowledge.